(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this paper is to understand the consumer perception of Counterfeit Luxury goods across ages and what consumer mentality triggers the consumption of these goods and can be associated to the causality to their rise in popularity